Improving the Quality of Human Resources and Organizational Management at Batik Nologaten MSMEs - Yulita Livrika; Audita Nuvriasari (Asian Journal of Community Services, 2023)
Batik as an Indonesian cultural heritage, especially for Batik Nologaten with typical Sleman batik. The purpose of this internship program is to apply knowledge and skills in accordance with the fields of students so that they can contribute to help the development of Batik Nologaten MSMEs. Methods of carrying out activities through counseling and training. The results of this work program activity are increasing the knowledge and skills of Batik Nologaten MSMEs in improving the quality of human resources in Batik Nologaten MSMEs on skills development, increasing knowledge of batik production, and strengthening managerial skills. In addition, organizational management also focuses on structured management, management process, and reporting systems.